Bioremoval of lead in industrial wastewater by microalgae - Ranitha, M. (Taylor's University, 2016)
The removal of heavy metals from our environment especially wastewater is now shifting from the use of conventional removal method such as chemical precipitation, coagulation and membrane filtration to the use of bioremoval method. The presence of heavy metals in the environment is of major concern because of their toxicity, bioaccumulating tendency, and threat to human life and the environment. In recent years, many low cost sorbents such as microalgae, fungi bacteria and lignocellulosic agricultural by-products have been investigated for their biosorption capacity towards heavy metals. In this project, the focus is on bioremoval of heavy metals in wastewater using marine microalgae. The study will be emphasize on the efficiency of two marine microalgae named Nannochloropsis oculata and Tetraselmis chuii in treating the Lead (Pb) content in industrial wasterwater. An experiment on the effect of various Pb concentration (10/20/40/60/80/100mg/L) towards the microalgae has been studied. The obtained result showed that the content of chlorophyll-A in the microalgae sample, after 7 days of exposures to Pb, decreased as the Pb concentration increased. Besides that, Tetraselmis chuii was found to be more sensitive compared to Nannochloropsis oculata where both were able to tolerate the Pb concentration of up to only 20mg/L and 60mg/L, respectively. Â© School of Engineering, Taylorâs University.